Centromere Emergence in Evolution - Ventura, Mario; Archidiacono, Nicoletta; Rocchi, Mariano (Genome Research, 2001)
Evolutionary centromere repositioning is a paradox we have recently discovered while studying the conservation of the phylogenetic chromosome IX in primates. Two explanations were proposed: a conservative hypothesis assuming sequential pericentric inversions, and a more challenging assumption involving centromere emergence during evolution. The complex evolutionary history showed by chromosome IX did not allow us to clearly distinguish between these two hypotheses. Here we report comparative studies of chromosome X in two lemur species: the black lemur and the ringtailed lemur. The X chromosome is telocentric in the black lemur and almost metacentric in the ringtailed lemur. The marker order along these chromosomes, however, was found to be perfectly colinear with humans. Our data unequivocally point to centromere emergence as the most likely explanation of centromere repositioning.
10.1101/gr.152101